Percepção de profissionais da Atenção Primária à Saúde acerca das desinformações reproduzidas durante a pandemia de Covid-19 - Bervian, Newton Gabriel de Andrade (2023)
Disinformation is the expression of an old phenomenon in history, which took shape with the emergence of globalization and the advent of social networks. During the Covid-19 pandemic, combating disinformation has become strategic for health professionals, considering the serious effects of the virus and the disease. The general objective of the present study was to understand the perception of health professionals in Primary Health Care in a municipality in westermost Santa Catarina regarding misinformation related to Covid-19 disseminated during the pandemic period and its repercussions on health care. As specific objectives: to understand how scientific productions in the health area have addressed the problem of misinformation regarding the Covid-19 pandemic; to analyze the understanding of health professionals about the concept of disinformation in health and fake news; identify the main misinformation conveyed during the period of the Covid19 pandemic reproduced by subjects assisted by the PHC; understand how misinformation related to Covid-19 influenced the routines of health professionals; as well as, to verify how health professionals acted in the face of misinformation brought by the subjects who sought health care. This is a case study, combining an integrative literature review and a descriptive exploratory study, with a quantitative and qualitative approach, with participants from higher education health professionals who worked in Primary Health Care, in a municipality in westermost Santa Catarina. Catarina, Brazil. The results were organized into two articles, the first is an integrative literature review, in which 15 Brazilian articles were selected, published from 2020 to March 2022 that contained the terms “Desinformação” and “Covid-19” for analysis. The concepts of infodemic and disinfodemia were highlighted, explaining the discussion about polarization and the clash of narratives, reinforced by the dubious performance of the federal government during the pandemic. The role of journalism in acting against this phenomenon was highlighted as fundamental, as well as an eventual regulation of the media by the State. Furthermore, it is understood that there are few related empirical studies on the subject, and research is needed to broaden this view. Article two is the result of exploratory research, in which higher-level primary health care professionals were approached through an online survey. The study included 20 professionals, who associated disinformation with fake news and false information, and perceived mainly disinformational content reproduced by users as related to vaccination and treatment of the disease. It can be seen that misinformation had a negative impact on the work of professionals and on health care. It is understood as essential to strengthen Primary Health Care, as well as to invest in ongoing training processes for professionals to combat disinformation in health.